New models for improving teaching and training in engineering and technology transfer in South Africa - Snyman, L.W.; Kruger, D. (South African Journal of Higher Education, 2020)
South Africa is in great need of improving the effectiveness of engineering and technical tuition and also enhancing technology transfer from universities to industry, the commercial sector and communities. These practices can create new job opportunities and increase the level of living standard of populations at all levels. This article highlights some models that were recently implemented at the School of Engineering of the University of South Africa in Johannesburg in order address these challenges. These included new on-line teaching methodologies with an emphasis on group work and project-based outcomes, new methodologies of work-integrated learning, the creation of an undergraduate-postgraduate dualism, a focus on innovation and product development at graduate level, and the creation of community entrepreneurship winter school programs. Measures as implemented contributed to an increase in enrolment rates 10 per cent over four years from the online teaching programmes in the diploma programme, enhanced placement of work integrated students, and eventually increased the graduation rate at graduate level by about 15 per cent over four years. Several new small companies have been created from winter school programmes.